Estimation of Interpupillary Distance Based on Eye Movements in Virtual Reality Devices - Jeong-Sik Kim (IEEE, 2021)
A mismatch between the interpupillary distance (IPD) and inter-optical system distance (IOSD) in virtual reality (VR) applications can lead to discomfort. The IOSD must be adjustable according to the user’s IPD to solve this issue. In this study, we investigate IPD estimation methods by tracking eye movements such as conjugate eye movement (CEM) and vergence. We hypothesize that the distance between the two pupils maintained during the CEM and is identical to the IPD. The vergence-based method induces eye divergence and determines the IPD as the maximum distance between pupils. Experiments with visual stimuli to induce CEM and divergence were conducted. The average errors of the estimated IPDs for the CEM-based and vergence-based methods were 2.06 and 1.30 mm, respectively. Furthermore, the analysis results show that the proposed methods can effectively reduce the IPD-IOSD difference and are especially helpful for users with a small IPD. If the IOSD is adjusted to the IPD estimated by the proposed methods, then VR discomfort can be eliminated.